Comprehensive transcriptome and improved genome annotation of Bacillus licheniformis WX‐02. Issue 18 (29th July 2015) - Guo, Jing; Cheng, Gang; Gou, Xiang-Yong; Xing, Feng; Li, Sen; Han, Yi-Chao; Wang, Long; Song, Jia-Ming; Shu, Cheng-Cheng; Chen, Shou-Wen; Chen, Ling-Ling
Abstract : The updated genome of Bacillus licheniformis WX‐02 comprises a circular chromosome of 4 286 821 base‐pairs containing 4512 protein‐coding genes. We applied strand‐specific RNA‐sequencing to explore the transcriptome profiles of B. licheniformis WX‐02 under normal and high‐salt conditions (NaCl 6%). We identified 2381 co‐expressed gene pairs constituting 871 operon structures. In addition, 1169 antisense transcripts and 90 small RNAs were detected. Systematic comparison of differentially expressed genes under different conditions revealed that genes involved in multiple functions were significantly repressed in long‐term high salt adaptation process. Genes related to promotion of glutamic acid synthesis were activated by 6% NaCl, potentially explaining the high yield of γ‐PGA under salt condition. This study will be useful for the optimization of crucial metabolic activities in this bacterium. Abstract : The genome sequence and annotation of B. licheniformis WX‐02 was updated. Many asRNAs were found to be conditionally regulated and greatly repressed under salt condition. The changes in the expression levels of asRNAs and their corresponding sense genes were not related. Genes involved in multiple functions were significantly repressed under salt condition. Genes related to the high yield of γ‐PGA were induced by 6% NaCl.